Contemporary Logic Design - Katz, Randy H., 1955-; Borriello, Gaetano (Upper Saddle River, N.J. : Pearson Prentice Hall, 2005)
"Although the complexity of designs is necessitating ever more powerful abstractions, the fundamentals remain unchanged. The contemporary digital designer must have a much broader understanding of the discipline of computation, including both hardware and software. This broader perspective is present in this second edition."--BOOK JACKET.
Ch. 1. Introduction -- Ch. 2. Combinational logic -- Ch. 3. Working with combinational logic -- Ch. 4. Combinational logic technologies -- Ch. 5. Case studies in combinational logic design -- Ch. 6. Sequential logic design -- Ch. 7. Finite state machines -- Ch. 8. Working with finite state machines -- Ch. 9. Sequential logic technologies -- Ch. 10. Case studies in sequential logic design -- App. A. Number systems -- App. B. Basic electronics -- App. C. Flip-flop types.
Includes bibliographical references and index.
PB
Keywords: Electronic digital computers -- Circuits -- Design; Integrated circuits -- Very large scale integration -- Design -- Data processing; Logic design -- Data processing; Computer-aided design